Determination of crustal deformations based on GPS observing-session duration in Marmara region, Turkey - Demir, D. O.; Dogan, U. (ELSEVIER SCI LTD, 2014)
This paper reports on the estimation of changes of a GPS-based crustal deformation field as function of the observing session duration. This investigation was carried out on the Marmara Continuous GPS Network (Marmara region) by using UPS data collected on a set of 10 stations during the period 2002.50-2005.47 The GPS observations were processed in the ITRF 2005 reference frame using Bernese v5.0 software. Main results indicate that GPS data observation periods of 24 h are significantly more accurate than estimates determined from the short observing session. The squared sum of residuals for the 4-h data set (between 12:00 and 16:00 local time) are larger than the other data sets, probably due to the higher ionospheric effects during this time. Also, the deformation pattern obtained from the results of 8 h or more of the GPS data observations as depends on baseline length approaches to the deformation obtained from the results of 24 h GPS data observations. (C) 2013 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: GPS; Crustal deformation; Marmara region; Observing-session duration; GLOBAL POSITIONING SYSTEM; RELATIVE POSITIONS; EARTHQUAKE; ACCURACY; VELOCITY; IZMIT; Engineering; Astronomy & Astrophysics; Geology; Meteorology & Atmospheric Sciences